Depression in people with epilepsy in West China: Status, risk factors and treatment gap. (March 2019) - Li, Qian; Chen, Deng; Zhu, Li-na; Wang, Hai-jiao; Xu, Da; Tan, Ge; Zhang, Yu; Liu, Ling
Highlights: To evaluate the prevalence of depression in epileptic patients in West China. To assess the suicide risk in people with epilepsy (PWE) in West China. To explore the related risk factors of suicidality and comorbid depression in PWE. To evaluate the treatment gap of comorbid depression in PWE in West China. Abstract: Purpose: To evaluate the prevalence, suicidality and treatment gap (TG) of depression in people with epilepsy (PWE) in West China, and to explore the related risk factors. Methods: A consecutive cohort of PWE from West China Hospital was recruited. The Chinese version of the Neurological Disorders Depression Inventory for Epilepsy scale was used to assess depression and suicidality. Prevalence and TG of depression were calculated. Logistic regression analysis was used to assess risk factors of depression and suicidality. Results: Among a total of 461 participants, there were 29.9% with depression and 15.8% had suicidality. Being female, an unmarried status, disease course, seizure frequency, seizure occurrence in the last 6 months, and focal impaired awareness seizure were risk factors for depression. Depression was an independent risk factor for suicidality. The TG of depression was 72.5%. The TG was larger in the 30–40 year age group, in rural populations, and among those with a disease course between 5 and 10 years. The TG figures dropped with increasing annual family income. Conclusions: The prevalence of depression and the rate of suicide risk for PWE in West China are high. A large TG for depression exists in PWE. Clinicians should focus on depression and suicidality for PWE and identify the related risk factors in a timely manner so as to reduce the incidence of depression and suicide. Management including public education as well as professional training of neurologists are necessary to fill the TG.